Debunking the myth of money as motivator in a multigenerational workforce - Teng, Lee Su; Jayasingam, Sharmila; Zain, Khairuddin Naim Mohd (Universiti Putra Malaysia, 2018)
Granting an annual increment is the norm in Asian countries. Organisations spend millions on salaries, hoping for better performance. Undeniably, money is a crucial necessity for all. However, can it motivate every individual to work harder or to perform better at a job? Is the thought that everyone is money driven a misguided perception? This question is becoming increasingly pertinent with every change to workforce demographics as workers of newer generations come on board. With Baby Boomers, Generation X and Generation Y working side by side in the same space, workers are no longer a homogenous group. Today's workforce is the most diverse in history. Hence, the purpose of this study is to explore the truth of the perception that money is a motivator for good performance at work and to discover the actual motivators to work well of each generation. The findings confirm that money is perceived as the motivator for all the three generations. However, each generation is also driven by other specific motivators. With a multigenerational workforce, employers will need to take these motivators into consideration.